Butler, Mo., Rev. Ordinances ch. 15, art. 1, no. 18, §§ 44-45 (1906) - (:unkn) unknown (My University, 1906)
§If any person shall carry concealed upon or about his person any deadly or dangerous weapon, or shall go into any church or place where people have assembled for religious worship, or into any school-room or place where people are assembled for educational, literary, or social purposes, or to any election precinct on any election day or into any court room during the sitting of court, or into any other public assemblage of persons met for any lawful purpose, other than for militia drill or meeting called under the militia law of this state, having upon or about his person any kind of fire-arms, bowie-knife, dirk, dagger, slung-shot or other deadly weapon or shall in the presence of one or more person, exhibit any such weapon in a rude, angry, or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated, or under the influence of intoxicating drinks, or shall directly or indirectly, sell or deliver, loan or barter, to any minor any such weapon, without the consent of the parent or guardian of such minor, he shall, upon conviction, be punished by a fine of not less than fifty nor more than two hundred dollars, or by imprisonment in the city jail not less than five days nor more than six months, or by both such fine and imprisonment.
Keywords: BRANDISHING; CARRY - CONCEALED; SENSITIVE PLACES; TRANSFER - MINORS